The Result of Learning Management by Using Problem Based Learning ‎towards Prayer Practice Skills on Islamic Studies Subject for Secondary ‎School Students, Year 1‎ - อีแมดะซอ มูฮัมหมัดฟัรกีย์; เฮงยามา มูหำมัดสุใหมี; โต๊ะแม ยามีละห์ (Al-HIKMAH Journal, 2021)
Abstract This research has the objective 1) To develop and find effective learning management plan by using problem-based problems on prayer practice skills. 2) to develop problem-based prayer practice skills 3) To compare students’ academic achievement before and after class. Using the problem as the base 4) To assess the satisfaction of learners from studying the Islamic Studies course on learning management by using problem-based problems on prayer practice skills. Target groups used in this research are Secondary School Students, Year 1‎ Ban KotaBaru School KotaBaru district, Raman Amphoe, Yala Province Semester 2, Academic Year 2020, 20 students By using a specific random method (Purposive Sampling) The research instruments included 1) problem-based learning management plan There are 8 Islamic Studies courses in total of 8 hours. 2) The Salat Practice Skill Evaluation Form Using a problem-based learning management model towards prayer practice skills Secondary School Students, Year 1 Ban KotaBaru School It is a skill assessment form for prayer practice, 8 forms, 8 assessments, learning management plans, 10 points per plan. 3) a test to measure academic achievement Secondary School Students, Year 1 Ban KotaBaru School Using problem-based learning management The test is a multiple choice, with 40 questions 4 options. 4) The Student Satisfaction Evaluation Question-Based Learning Management Questionnaire on Prayer Practice Skills Secondary School Students, Year 1 Ban KotaBaru School That use learning management based on 10 problems The statistics used for data analysis are Mean, Percentage, Standard Deviation and T-Test Dependent The results of the research were as follows Result for E1 / E2 of Islamic Studies Learning Plan For students in Secondary School Students, Year 1, Ban KotaBaru School By using problem-based learning management Come to compare the learning achievement of the learners According to the 80/80 standard, it was found that the learners were able to score correctly during the course of 80.25 percent and that the learners were able to score correctly after 8 percent. 0.50 Therefore, this learning management plan As effective as 80. 25 / 80.50 Assess the prayer practice skills gained from using the problem-based learning management plan. For Secondary School Students, Year 1 students after classes have practice prayer skills Significantly higher at the .05 level Academic achievement before and after learning through problem-based learning management on prayer practice skills. Course in Islamic Studies For students in the secondary school year 1 after studying, have a higher score than before studying With statistical significance at the .05 level. The satisfaction of the learners who learned through problem-based learning management on the practice of prayer skills. Course in Islamic Studies For Secondary School Students, Year 1 after studying, the score is higher than before studying. With statistical significance at the .05 level. Keywords: Problem-based learning management / Prayer practice skills / Islamic studies course / Secondary School Students, Year 1